FIRST FINDINGS OF THE VOLCANIC ROCKS IN SVECOFENNIDES OF THE LADOGA REGION AND THEIR AGE - Baltybaev Sh.K.; Levchenko O.A.; Galankina O.L. (My University, 2004)
Svecofennides occupy a vast territory in the southeastern Baltic Shield. They are distributed mainly in the Scandinavian and Baltic countries. In Russia, they are developed only within the Ladoga region. Scandinavian geologists have shown that tectonic relations between Svecofennian rocks and the adjacent Archean infracrustal complex can be characterized in terms of the ocean-continent boundary. Based on U-Pb zircon dating of the underlying amphibolites of the Sortavala Group, the age of metaturbidites of the Ladoga region is estimated to be no older than 1.96 Ga [8]. The upper age was constrained by the crystallization age of norite-enderbite rocks crosscutting the metaturbidite sequence (1.88-1.89 Ga). The U-Pb dating of zircons and monazites from metamorphic rocks and migmatites suggests a metamorphic peak of the turbidite sequences at 1.87-1.88 Ga.